The Potential Benefit by Application of Kinetic Analysis of PET in the Clinical Oncology. (26th December 2012) - Takesh, Mustafa
Abstract : PET is an appropriate method to display the functional activities in target tissue using many types of traces. The visual assessment of PET images plus the semiquantitative parameter (SUV) are the main diagnostic standards considered in identifying the malignant lesion. However, these standards lack occasionally the proper specificity and/or sensitivity. That emphasizes the importance of considering supplemental diagnostic criteria such as the kinetic parameter. The latter gives the way to image the ongoing metabolic processes within the target tissue as well as to identify the alterations occurring at the microscale level before they become observable in the conventional PET-imaging. The importance of kinetic analysis of PET imaging has increased with newly developed PET devices that offer images of good quality and high spatial resolution. In this paper, we highlighted the potential contribution of kinetic analysis in improving the diagnostic accuracy in intracranial tumour, lung tumour, liver tumour, colorectal tumour, bone and soft tissue tumours, and prostate cancer. Moreover, we showed that the appropriate therapy monitoring can be best achieved after considering the kinetic parameters. These promising results indicate that the kinetic analysis of PET imaging may become an essential part in preclinical and clinical molecular imaging as well.